Rancang Bangun Sistem Sales Visit Report Berbasis Web Menggunakan Metode RAD (Studi Kasus: PT Petrindo Semesta) - Ubaydillah; Bobi Agustian (CV. Multi Kreasi Media, 2025)
The rapid development of information systems has permeated corporate management, including at PT Petrindo Semesta, an oil and gas industry supply and maintenance company with high sales visit activity. Currently, the management and reporting of sales visits, which still rely on a manual logbook, pose significant constraints, such as difficulty for HRD in compiling visit hours, inefficient logbook access for sales personnel, and insufficient monitoring of visit outcomes. Therefore, this research aims to design and build a web-based sales visit report system using the Rapid Application Development (RAD) method, which is expected to simplify the recording of check-in and check-out times for HRD, provide easier logbook access, and facilitate report monitoring by supervisors, thereby making the recapitulation process more systematic, logbook access easier, and reports effectively actionable.